ANALYSIS OF DIGITAL LITERACY IN IMPROVING THE PERFORMANCE OF VILLAGE APPARATUS IN PADASUKA VILLAGE KUTAWARINGIN - Alda Ramadhika; Sri Maesin Mu'awaroh (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
Abstract. This research focuses on analyzing how digital literacy plays a role in improving the performance of village officials in Padasuka Village. The main objective is to identify how the development of digital literacy of village officials and the things that influence it, and analyze its impact on the performance of village officials in providing services to the community. This research applies descriptive qualitative methods with data collection techniques through interviews, observations, and literature review, with data analysis methods through reduction, data presentation, and conclusion drawing. The unit of analysis of this research is the staff of the Padasuka Village office. The findings of this study reveal that digital literacy has been running well and has a positive impact on the performance of village officials in Padasuka Village, especially in improving village services, speeding up work, reducing and monitoring error rates, as well as making it easier to share information online. Although there are access limitations, as well as a lack of skills in the use of digital technology, there are also external factors from the community that lack awareness of the importance of digital literacy. In this case, the recommendation given is the need to maximize support from all parties, both the community and the central government.